1990
DOI: 10.1002/cne.902980306
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of sympathetic preganglionic neurons in the neonatal rat spinal cord: An intracellular horseradish peroxidase study

Abstract: Understanding the central neural control of autonomic functions requires a knowledge of the morphology of the preganglionic neurons, for the location of the dendritic arborizations of these neurons will indicate which central pathways may have access to them. In the present study, individual sympathetic preganglionic neurons in the neonatal rat spinal cord have been examined by the intracellular injection of horseradish peroxidase (HRP) in an in vitro preparation. Seventeen HRP-labeled preganglionic neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Consistent with NK-1 binding studies (Buck et al, 1986;Charlton and Helke, 1985;Helke et al, 1986;Shults et al, 1984;Yashpal et al, 19901, we found SPR-immunoreactive neurons in each of the three major regions of the rat spinal cord that contain sympathetic preganglionic neurons (SPN), the intermediolateral cell column, the intercalated nucleus, and the central autonomic nucleus. The immunohistochemical analysis revealed that many of the SPR-immunoreactive neurons had dendrites that coursed mediolaterally from the IML to the central canal, which is consistent with a morphological analysis of antidromically activated SPNs in the IML (Forehand, 1990). Heavily labeled dendrites in the and dendritic surfaces of labeled neurons and that most of the labeled membrane is not apposed by SP-immunoreactive terminals (Liu et al, 1994).…”
Section: Laminar Distribution Of Spr-immunoreactive Neuronsmentioning
confidence: 56%
“…Consistent with NK-1 binding studies (Buck et al, 1986;Charlton and Helke, 1985;Helke et al, 1986;Shults et al, 1984;Yashpal et al, 19901, we found SPR-immunoreactive neurons in each of the three major regions of the rat spinal cord that contain sympathetic preganglionic neurons (SPN), the intermediolateral cell column, the intercalated nucleus, and the central autonomic nucleus. The immunohistochemical analysis revealed that many of the SPR-immunoreactive neurons had dendrites that coursed mediolaterally from the IML to the central canal, which is consistent with a morphological analysis of antidromically activated SPNs in the IML (Forehand, 1990). Heavily labeled dendrites in the and dendritic surfaces of labeled neurons and that most of the labeled membrane is not apposed by SP-immunoreactive terminals (Liu et al, 1994).…”
Section: Laminar Distribution Of Spr-immunoreactive Neuronsmentioning
confidence: 56%
“…The described morphology was shown to be typical for SPNs in the lateral horn (Forehand, 1990;Shen & Dun, 1990) and has already been used as a criterion for positive identification of these neurones by other authors (Pickering, Spanswick & Logan, 1991). In addition, we have been able to label SPNs retrogradely (Y. Larmet, J. Krupp & P. Feltz, unpublished observations) after injection of 1,1'-dioctadecyl-3,3,3',3'-tetramethylindocarbo-cyanine perchlorate (DiI) into the adrenal medulla.…”
Section: Morphology Of Recorded Cellsmentioning
confidence: 72%
“…Since the dendritic processes of SPNs extend several hundred micrometres away from the cell soma (Bacon & Smith, 1988;Forehand, 1990), errors may arise from inadequate voltage control in these distal regions. If the synaptic currents we recorded originated in these regions, the time course and amplitude of these currents would probably be distorted by the filtering of the RC network of the distal dendrites.…”
Section: Site Of Origin Of Synaptic Currentsmentioning
confidence: 99%
“…Other investigators using Golgi staining or intracellular labeling with HRP to study sympathetic preganglionic neurons in the cat have found no evidence of axon collaterals (13,21). Similarly, previous experiments on the sympathetic system in other species, including the neonatal rat (22,23) and the pigeon (24), would indicate collaterals on sympathetic preganglionic neurons are rare and are limited in structure and extent. But, in view of the current results, it might be worthwhile to explore these regions again by using intracellular labeling with neurobiotin.…”
Section: Discussionmentioning
confidence: 91%